Factors associated with mpox awareness among men who have sex with men recruited through the internet: a cross-sectional survey in China - Yun Fu; Weiyong Chen; Rui Yuan; Xing Wang; Zhongrong Yang (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to provide a scientific basis for formulating mpox prevention and control strategies for men who have sex with men (MSM) by analyzing the associated factors.MethodsWe conducted online surveys with individuals recruited through the Internet in May 2024. Univariate and multivariate logistic regression analyses were used to identify factors influencing knowledge about mpox.ResultsIn the 604 participants surveyed, the mpox knowledge rate was 62.91%. Multivariate logistic regression analysis results showed that the following factors were associated with higher levels of mpox knowledge (p < 0.05): age 30 years and above, education level of college or above, average monthly income ≤6,000 CYN, belief that using rush poppers increases the risk of HIV infection, recent exposure to HIV or mpox information through online media, and recent receipt of HIV or mpox prevention services.ConclusionMpox-prevention knowledge should be promoted among individuals who have lower education levels, while the dissemination of information on HIV and mpox through online media should be increased to reduce the risk of mpox or HIV infection among this population.